A Case Study On Augmented Reality Applications For Chemistry Subject Using Heuristic Evaluation - Mohd Rafee, Nur Safura; Mohammed, Norazlin (Penerbit Universiti Teknikal Malaysia Melaka, 2021)
Augmented Reality (AR) has been acknowledged as a method that is effective in learning and becomes complementary to conventional learning, especially for Chemistry subjects. However, chemistry textbooks only consist of images and formulas; thus, students have difficulties understanding the concept, which may lead to misconceptions in understanding the topic. Therefore, this research focuses on developing and designing an Augmented Reality application for Chemistry subjects since no specific guidelines in developing an AR for education, especially for Chemistry. This paper aims to study the current heuristic guidelines and evaluating the existing Augmented Reality application for Chemistry subjects in order to determine the problem using Heuristic Evaluation. Kubu AR Kimia T5 was chosen as the existing application to be used in the Heuristic Evaluation process because Heuristic Rules are used by multiple researchers. The improvement of AR application developed based on the evaluation received. A custom set of the improvements heuristic principles was developed in this study and as a new guideline in designing other AR applications for Chemistry subjects in the future. In a conclusion, user acceptance tests take place to measure the effectiveness of AR using Heuristic Evaluation. The AR application that was developed is part of the educational tool in learning Chemistry subjects in high school and assist in learning and teaching methods to provide a better understanding of learning chemistry.